Hubungan Pengalaman Bencana Dengan Kesiapsiagaan Masyarakat Dalam Menghadapi Bencana Erupsi Gunung Semeru Di Desa Sumbermujur Kecamatan Candipuro Lumajang - Fitriana, Mutiara Dwi; Rohmah, Nikmatur; Hamid, Mohammad Ali (Peneliti.net, 2025)
The recurrent eruptions of Mount Semeru in Sumbermujur Village, Candipuro District, Lumajang, have caused extensive damage and claimed numerous lives. This study delves into the relationship between disaster experience and community preparedness in confronting Mount Semeru eruptions. Employing a descriptive correlational design with a quantitative approach, the study utilizes purposive sampling, selecting 201 respondents from the Sumbermujur Village population. The research instrument comprises a questionnaire consisting of 30 Likert scale questions to gauge disaster experience and community preparedness. Validity and reliability tests affirm the instrument's validity and reliability. Pearson correlation analysis reveals a significant correlation between disaster experience and community preparedness in facing Mount Semeru eruptions (p-value < 0.05). This indicates that the more disaster experience communities possess, the higher their level of preparedness. Based on these findings, the study recommends enhancing disaster education and simulation programs by the government and stakeholders to elevate community preparedness in confronting Mount Semeru eruptions.